Rapid review of virus risk communication interventions: Directions for COVID-19. Issue 8 (August 2021) - Winograd, Darren M.; Fresquez, Cara L.; Egli, Madison; Peterson, Emily K.; Lombardi, Alyssa R.; Megale, Allison; Tineo, Yajaira A. Cabrera; Verile, Michael G.; Phillips, Alison L.; Breland, Jessica Y.; Santos, Susan; McAndrew, Lisa M.
Highlights: Risk communication for viruses can be efficacious. Results highlight the complexities of risk communication. Risk communication for HIV/AIDS was more consistently efficacious as compared to influenza. Various risk communication approaches were effective. Tailoring risk communication to a population may be more efficacious. Abstract: Objective: In response to COVID-19, we conducted a rapid review of risk communication interventions to mitigate risk from viruses to determine if such interventions are efficacious. Methods: We searched for risk communication interventions in four databases: Medline, PsycInfo, the ProQuest Coronavirus Research Database, and CENTRAL. The search produced 1572 articles. Thirty-one articles were included in the final review. Results: Results showed risk communication interventions can produce cognitive and behavior changes around viruses. Results were more consistently positive for interventions focused on HIV/AIDS as compared to influenza. There was no consistent best intervention approach when comparing peer health, audio/visual, and intensive multi-media interventions. Tailoring risk communication toward a target population, in comparison to not tailoring, was related to better outcomes. Conclusion: The results suggest that risk communication interventions can be efficacious at reducing risk from viruses. They also highlight the complexity of risk communication interventions. Additional research is needed to understand the mechanisms that lead risk communication to reduce risk from viruses. Practical value: Results support risk communication interventions to reduce risk from viruses.